2017
DOI: 10.1177/0145445517741474
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injurious Behavior in Children With Developmental Disabilities: A Systematic Review of Behavioral Intervention Literature

Abstract: We reviewed single-case research studies examining the effects of behavioral interventions for self-injurious behavior (SIB) in young children with autism and developmental disabilities. Systematic searches of electronic databases, journals, and reference lists identified 46 studies (66 participants younger than the age of 12) meeting inclusion criteria. Studies were examined based on (a) participant demographics, (b) topography and function of SIB, (c) type of functional behavior assessment (FBA), (d) interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 108 publications
(114 reference statements)
2
21
0
Order By: Relevance
“…Conversely, the current results revealed that SIB treatment studies focused more on SIB maintained by automatic reinforcement. These data are consistent with the behavior treatment review by Gregori et al (2017) in which adults diagnosed with IDD were found to most frequently have SIB maintained by automatically reinforcement. Thus, taken together, these data suggest that perhaps there has been a shift in research priority to treat more complex SIB maintained by automatic reinforcement (e.g., , Hagopian et al, 2017.…”
Section: Functional Assessment and Functions Of Sibsupporting
confidence: 88%
“…Conversely, the current results revealed that SIB treatment studies focused more on SIB maintained by automatic reinforcement. These data are consistent with the behavior treatment review by Gregori et al (2017) in which adults diagnosed with IDD were found to most frequently have SIB maintained by automatically reinforcement. Thus, taken together, these data suggest that perhaps there has been a shift in research priority to treat more complex SIB maintained by automatic reinforcement (e.g., , Hagopian et al, 2017.…”
Section: Functional Assessment and Functions Of Sibsupporting
confidence: 88%
“…To date, effective interventions for challenging behavior support the use of functional analysis and behavioral interventions based in the science of applied behavior analysis (ABA; Baer, Wolf, & Risley, 1968;Cooper, Heron, & Heward, 2007;Emerson et al, 2001;Iwata, Dorsey, Slifer, Bauman, & Richman, 1994). Function-based interventions including noncontingent reinforcement (providing reinforcers on a fixed-time schedule to decrease motivation to engage in challenging behavior), teaching appropriate behavior (i.e., functionally-equivalent replacement behavior), positive reinforcement contingent on appropriate behavior, extinction (withholding consequences for challenging behavior), and positive and negative punishment strategies have documented effectiveness in significantly reducing challenging behavior (Davis & Rispoli, 2018;Erturk, Machalicek, & Drew, 2018;Mulligan, Healy, Lydon, Moran, & Foody, 2014). Caregivers' involvement in treatment plays a critical role in generalizing and maintaining treatment outcomes in natural settings, and caregivers can implement behavioral treatment with high fidelity to improve the child's challenging behavior (Gerow et al, 2018;Lang et al, 2013).…”
mentioning
confidence: 99%
“…During this time, researchers and professionals begin to rely primarily on multicomponent behavior intervention plans and antecedent interventions, which are based on manipulation of motivational variables and stimulus control (Carr & Carlson, 1993;Carr et al, 1990). The treatment of serious challenging behavior (e.g., aggression, pica or the ingestion of inedible materials) for some individuals with IDD does require the use of aversives or restrictive procedures to prevent harm (Hanley et al, 2005;Lerman & Vorndran, 2002); however, the use of aversives or restrictive procedures is now uncommon in ABA intervention research even when addressing serious challenging behavior (Erturk et al, 2018;Kahng et al, 2002).…”
Section: Punishmentmentioning
confidence: 99%